2008
DOI: 10.1080/03093640701838190
|View full text |Cite
|
Sign up to set email alerts
|

Considerations for developing an evidenced-based practice in orthotics and prosthetics

Abstract: Evidence-based practice has become somewhat of a catchphrase over the past ten years. In this paper evidence-based practice is defined and its importance for the development of the prosthetics and orthotics profession is highlighted. The authors suggest that evidence-based practice needs to be prioritized within the profession and that a cultural change needs to be initiated which supports clinicians in incorporating research findings into their daily practice. In addition, the authors highlight the need for p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
49
0
2

Year Published

2009
2009
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 39 publications
(55 citation statements)
references
References 24 publications
(32 reference statements)
2
49
0
2
Order By: Relevance
“…22,23 In addition, Ramstrand and Brodtkorb 17 have suggested that clinicians lack the expertise to perform research, and this is supported here by the fact that only a few respondents held a master's degree and none a doctoral degree. To combat this barrier, Ramstrand and Brodtkorb 17 propose that 'evidence-based practice needs to be prioritized within the profession and that a cultural change needs to be initiated which supports the need for prosthetists/orthotists to become more active in generating research rather than relying on other professional groups to contribute to their professional body of knowledge'. While facilities generally appear to promote EBP and encourage clinicians to pursue new ideas, as well as providing financial support for conferences, there does appear to be a lack of encouragement for clinicians to pursue research.…”
Section: Discussionmentioning
confidence: 66%
“…22,23 In addition, Ramstrand and Brodtkorb 17 have suggested that clinicians lack the expertise to perform research, and this is supported here by the fact that only a few respondents held a master's degree and none a doctoral degree. To combat this barrier, Ramstrand and Brodtkorb 17 propose that 'evidence-based practice needs to be prioritized within the profession and that a cultural change needs to be initiated which supports the need for prosthetists/orthotists to become more active in generating research rather than relying on other professional groups to contribute to their professional body of knowledge'. While facilities generally appear to promote EBP and encourage clinicians to pursue new ideas, as well as providing financial support for conferences, there does appear to be a lack of encouragement for clinicians to pursue research.…”
Section: Discussionmentioning
confidence: 66%
“…As previously discussed, this may require a cultural shift by the P&O profession. 3 Strategies that have been successfully trialed to influence acceptance of EBP at the level of the user have employed techniques that involve clinicians themselves in the strategic development and evaluation phases. This ensures that clinicians remain as active participants in the process of change rather than passive recipients of information.…”
Section: Theoretical Frameworkmentioning
confidence: 99%
“…[1][2][3][4][5] To date, articles related to EBP in prosthetics and orthotics (P&O) have focused on defining terminology, 3 reviewing the state of EBP in P&O clinical practice and on identifying factors that influence the use of EBP in P&O clinical practice. [1][2][3]5 To date, no discussion or research has been dedicated to the practical process of introducing and sustaining EBP as part of clinicians' everyday routine. Christensen and Andrysek 5 suggest that strategic implementation may facilitate the use of EBP but highlight that little research is available from within the field of P&O.…”
Section: Introductionmentioning
confidence: 99%
“…9 In line with Sackett et al's 10 definition of evidencebased medicine (EBM), EBP in prosthetic rehabilitation is characterized as the process of integrating individual clinical expertise and patient values with the best available evidence from systematic research, in order to provide the best clinical care. [1][2][3][4] This definition comes across as attractive. It gives the impression that it is the 'simple' task of (rehabilitation) clinicians to combine original evidence produced in different research settings with their own individual clinical expertise including the individual needs of patients to whom they wish to give the best treatment.…”
mentioning
confidence: 99%
“…A number of practical barriers in performing EBP are to be dealt with, such as lack of high-level evidence in P&O, time constraints and workload demands experienced by clinicians and finally limited skills, knowledge and resources required to perform EBP. [1][2][3][4] Researchers interested in P&O point variously to limitations in both research and practice hindering the evidence-based integration process. A culture change is plead for, in which clinicians in P&O are to be educated as lifelong, self-directed learners and are encouraged to pursue relevant clinical research themselves.…”
mentioning
confidence: 99%